2023
DOI: 10.1029/2022ja031202
|View full text |Cite
|
Sign up to set email alerts
|

Proton Flux Variations During Solar Energetic Particle Events, Minimum and Maximum Solar Activity, and Splitting of the Proton Belt in the South Atlantic Anomaly

Abstract: The South Atlantic Anomaly (SAA) is an area where Earth's magnetic field is particularly low. This comes from the fact that the Earth's magnetic axis is tilted with respect to the Earth's rotation axis by an angle of approximately 11° and that the axis of the magnetic idealized dipole is located some 400 km away from the Earth's center (Brekke, 2013). As a consequence, the SAA is also a region where inner radiation belt particles can mirror at lower altitudes increasing the local particle flux.Unlike the geogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Next, we observe a phase-lag anti-correlation of the SAA surface with the solar activity. This anti-correlation is well known (Casadio & Arino, 2011;Dachev et al, 1999;Huston et al, 1998;Kuznetsov et al, 2010;Li et al, 2001;Pierrard et al, 2023;Qin et al, 2014). This can be explained in two ways.…”
Section: Global Surface Temporal Evolutionmentioning
confidence: 80%
“…Next, we observe a phase-lag anti-correlation of the SAA surface with the solar activity. This anti-correlation is well known (Casadio & Arino, 2011;Dachev et al, 1999;Huston et al, 1998;Kuznetsov et al, 2010;Li et al, 2001;Pierrard et al, 2023;Qin et al, 2014). This can be explained in two ways.…”
Section: Global Surface Temporal Evolutionmentioning
confidence: 80%
“…More recently, the large SEP event of September 2017 was investigated by Pierrard et al. (2023), who confirmed that solar protons could reach the inner belt but were immediately lost due to the following magnetic storm.…”
Section: Introductionmentioning
confidence: 94%
“…For instance, Pierrard et al (2014) observed the remaining trapped solar protons around the whole month of June 2013 between L = 4-5 after the intense SEP event in May 2013. More recently, the large SEP event of September 2017 was investigated by Pierrard et al (2023), who confirmed that solar protons could reach the inner belt but were immediately lost due to the following magnetic storm.…”
Section: Evidence From Observationsmentioning
confidence: 99%